Evaluation of the double mesh and intraperitoneal onlay mesh techniques in giant incisional hernias - Gülten Çiçek Okuyan; Mehmet Talu (National Scientific Medical Center, 2023)
Background: Giant incisional hernias are difficult to manage. The present study aims to comparatively evaluate the intraperitoneal onlay mesh (IPOM) technique to double-mesh repair techniques in patients with a midline abdominal wall incisional hernia larger than 15 cm (transvers width) that cannot be closed primarily. Material and methods: Patients who underwent repair surgery with the diagnosis of incisional hernia in our hospital between January 2017 and December 2019 were retrospectively evaluated. The repair was performed with open surgery using the IPOM technique in 19 patients and the double-mesh technique in 13 patients for 2 years to evaluate for postoperative complications, pain, and recurrence. Results: The mean age, gender distribution, body mass index, defect size, and American Society of Anesthesiologists scores were similar between the groups. The total rate of postoperative complications was 42.1% in Group A and 30.8% in Group B, with no significant difference between the groups (p > 0.05). Recurrence occurred in three patients (15.8%) in Group A, but it did not in Group B. Although the absence of recurrence in Group B was a remarkable finding, the difference was not statistically significant (p>0.05). Discussion: The IPOM and double-mesh techniques can be used safely to perform tension-free abdominal wall reconstruction in patients with complex and giant incisional hernias. However, the double-mesh technique may be preferred owing to its lower recurrence rate.